2016
DOI: 10.5213/inj.1630460.230
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Turkish Language Version of the International Consultation on Incontinence Questionnaire - Male Lower Urinary Tract Symptoms

Abstract: Purpose:Patients receiving treatment for benign prostate hyperplasia may have persistent storage symptoms. There has been increasing debate on the precision and accuracy of the International Prostate Symptom Score questionnaires over other questionnaires in evaluating all the complaints of lower urinary tract symptoms (LUTS). The aim of this study was to perform the validity and reliability analysis of the Turkish version of the Internatinal Consultation on Incontinence Questionnaire-Male LUTS (ICIQ-MLUTS).Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 12 publications
2
25
0
Order By: Relevance
“…After a detailed and rigorous psychometric evaluation, we have shown that the Chinese versions of the ICIQ‐MLUTS and ICIQ‐MLUTS LF are suitable, reliable, stable, and responsive to symptom changes, suggesting they are now available for clinical use. These results are consistent with previous studies …”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…After a detailed and rigorous psychometric evaluation, we have shown that the Chinese versions of the ICIQ‐MLUTS and ICIQ‐MLUTS LF are suitable, reliable, stable, and responsive to symptom changes, suggesting they are now available for clinical use. These results are consistent with previous studies …”
Section: Discussionsupporting
confidence: 94%
“…It takes patients approximately 10 to 15 minutes to complete both the questionnaires. The original version of the ICIQ‐MLUTS is in English, but it has been translated into many other languages, including Turkish, Danish, Dutch, French, German, Italian, Japanese, Spanish, and Persian . The ICIQ‐MLUTS has shown satisfactory metric properties and served as a useful instrument for the initial diagnosis, management, and patient follow‐up in such populations …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age of the sample in the present study was considerably younger than the original study; however, the reliability and internal consistency of the two studies was similar. In comparison to the Turkish version and Spanish version of MLUTS, the reliability and internal consistency of Persian version was lower and higher respectively …”
Section: Discussionmentioning
confidence: 74%
“…In comparison to the Turkish version and Spanish version of MLUTS, the reliability and internal consistency of Persian version was lower and higher respectively. 13,14…”
Section: Discussionmentioning
confidence: 99%